Zr/Rb XRF and calculated current velocities IODP Site 382-U1537 - Ronge, Thomas A (PANGAEA, 2025)
This dataset contains X-ray fluorescence (XRF) and calculated bottom current velocities for IODP Site U1537. The sediment cores were collected aboard the JOIDES Resolution in 2019 during IODP expedition 382 to the Antarctic Iceberg Alley. XRF measurements were conducted with an Avaatech core scanner in 2019 at the IODP Gulf Coast Repository in College Station, Texas. Following the method of McCave et al., 2006/2017, Sortable Silt measurements and XRF calibration was conducted at the Alfred-Wegener-Institute in Bremerhaven, Germany between late summer of 2020 and the end of 2021. The aim of this study is to provide a method of XRF-derived grain size and ultimately current velocity measurements that allows for the fast and reliable interpretation of long sediment cores.
Keywords: current velocity; IODP; sortable silt; Southern Ocean; XRF